Mulheres Grotescas: a subversão de estereótipos femininos em Ânsia Eterna, de Júlia Lopes de Almeida - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
This dissertation investigates the subversion of female stereotypes in the short stories of Ânsia Eterna (1903), by Júlia Lopes de Almeida, through an analysis of female characters marked by the grotesque. The research starts from the historical recognition of the erasure of women writers in the Brazilian literary canon and proposes a critical recovery of Júlia Lopes de Almeida’s work, whose literary production and intellectual contributions have been silenced despite their significance. Drawing on feminist theory (Scott, Beauvoir, Woolf, Showalter), literary theory (Iser, Jouve), and aesthetics of the grotesque (Kayser), this study examines how selected stories challenge gender roles, expose both symbolic and physical violence against women, and use the grotesque as a narrative strategy to provoke estrangement and critical reflection. The research demonstrates that, by portraying female characters who defy social and aesthetic expectations, Júlia Lopes de Almeida offers a powerful critique of the patriarchal structures of her time. Ânsia Eterna thus emerges as a literary work of remarkable aesthetic sophistication and political force, whose reading contributes to broadening perspectives on women’s place in Brazilian literature and the value of narratives that resist normative models.
Keywords: grotesco; feminino; violência; melancolia; subversão; grotesque; female; violence; melancholy; subversion; Estudos da Linguagem